Combination of G-CSF and AMD3100 Improves the Anti-inflammatory Effect of Mesenchymal Stem Cells on Inducing M2 Polarization of Macrophages Through NF-κB-IL1RA Signaling Pathway - Chen, Long; Zhang, Qian; Chen, Qin-Hua; Ran, Feng-Yin; Yu, Li-Mei; Liu, Xiu; Fu, Qiang; Song, Gong-Yu; Tang, Jun-Ming; Zhang, Tao (Frontiers in Pharmacology, 2019)
Mobilized peripheral blood-derived mesenchymal stem cells (PB-MSCs) mainly derived from bone marrow-derived MSCs (BM-MSCs) exert similar anti-inflammatory effect. However, the mechanism of anti-inflammatory effect of mobilized PB-MSCs by combination of G-CSF and AMD3100 remains unclear. Cultured rat PB-MSCs mobilized by G-CSF/AMD3100 have shown typical surface markers and potential for multiple differentiations, similarly to non-mobilized BM-MSCs. In a co-culture system, rat M0 type macrophages co-cultured with PB-MSCs have shown higher expression of M2 markers including CD206, Arg-1, IL-10 and CCL-22 than BM-MSCs, indicating that PB-MSCs induced greater M0 polarization to M2. Furthermore, compared with BM-MSCs, PB-MSCs in a co-culture system with lipopolysaccharide-induced M1 type macrophages more efficiently promoted M1 polarization to M2, accompanied by increasing expression of CD206, Arg-1, IL-10 and CCL-22 while decreasing expression of M1 markers including iNOS, TNF-α, IL-1β and IL-6, indicating that PB-MSCs triggered greater M1 polarization to M2. Subsequently, Polymerase chain reaction arrays showed higher expressions of both IL1rn and Tnfrsf11b in PB-MSCs versus BM-MSCs. In response to an inflammatory niche, such as TNF-α, PB-MSCs have shown higher expression and release of IL1RA, causing greater M2 polarization of macrophages, and the special effects may be almost entirely abolished through the neutralization antibody of IL1RA. Mechanistic studies determined that PB-MSCs showed higher levels NF-κBp65 and NF-κBp-p65 than BM-MSCs, which could be obviously enhanced by TNF-α. And the increased IL1RA expression by TNF-α in PB-MSCs could be markedly cancelled by NF-κB inhibitor PDTC. Interestingly, mimicking the mobilized PB-MSCs by combination of G-CSF and AMD3100 in vivo, BM-MSCs were treated with G-CSF and/or AMD3100 in vitro, showing the increased expressions of NF-κBp65 and IL1RA, which could be prominently abolished by PDTC. Therefore, targeting IL1rn, gene modification, or drug intervention for MSCs may provide a novel therapeutic strategy for human diseases, especially inflammatory diseases.